2019
DOI: 10.5005/jp-journals-10071-g23184
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy in Adult Intensive Care Unit: An ISCCM Expert Panel Practice Recommendations

Abstract: Background and Aim: Critically ill patients on mechanical ventilation undergo tracheostomy to facilitate weaning. The practice in India may be different from the rest of the world and therefore, in order to understand this, ISCCM conducted a multicentric observational study "DIlatational percutaneous vs Surgical tracheoStomy in intEnsive Care uniT: A practice pattern observational multicenter study (DISSECT Study)" followed by an ISCCM Expert Panel committee meeting to formulate Practice recommendations pertin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 146 publications
(199 reference statements)
3
18
0
Order By: Relevance
“…A study from 2006 showed that early tracheostomy in intensive care trauma patients improves resource utilisation, and delayed tracheostomy (> 14 days) was an independent predictor of prolonged ICU stay [ 9 ]. Similar findings are seen in systematic reviews and isolated studies, with most reporting statistically significant reductions in ICU length of stay and intubation-related complications when a tracheostomy is placed soon after intubation [ 9 – 11 ]. A study examining the effect of delayed tracheostomy (from the moment of decision to the procedure) on clinical outcomes found that shorter delays were also associated with successful weaning [ 12 ].…”
Section: Introductionsupporting
confidence: 70%
“…A study from 2006 showed that early tracheostomy in intensive care trauma patients improves resource utilisation, and delayed tracheostomy (> 14 days) was an independent predictor of prolonged ICU stay [ 9 ]. Similar findings are seen in systematic reviews and isolated studies, with most reporting statistically significant reductions in ICU length of stay and intubation-related complications when a tracheostomy is placed soon after intubation [ 9 – 11 ]. A study examining the effect of delayed tracheostomy (from the moment of decision to the procedure) on clinical outcomes found that shorter delays were also associated with successful weaning [ 12 ].…”
Section: Introductionsupporting
confidence: 70%
“…Scarcity of recommendations on necessity of FOB during PCDTs has led the authors to review more literature and only two such recommendations could be traced. 22 , 23 French expert panel have recommended routine use of FOB during PCDTs but their opinion was based on two nonrandomized and one randomized trials on just 60 patients, mostly from Western countries. 22 On the contrary, in a recently published multicentric study on 923 patients from India, the researchers have performed FOB in only 28.1% of all PCDTs, although they have mentioned that the use of FOB may reduce hemorrhagic complications during PCDT.…”
Section: Discussionmentioning
confidence: 99%
“… 24 The Indian Society of Critical Care Medicine (ISCCM) expert panel has also published a practice recommendation in 2020 which mentions that FOB can be used during PCDT if available but it does not decrease the incidence of complications during PCDTs. 23 So, to be in sync with recent pieces of evidence, we wish to state that the use of FOB may be desirable but it is not mandatory during PCDT. MS-PCDT can be a safe and effective alternative to FOB-guided PCDTs.…”
Section: Discussionmentioning
confidence: 99%
“…The French Society of Intensive Care [ 15 ] guidelines established a weak recommendation based on a study in 60 patients in which endoscopic guidance was associated with fewer minor complications. The Indian Society of Critical Care Medicine expert panel states that fiberoptic bronchoscope may be used, whenever available to aid PDT although it does not reduce the rate of complications [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The duration of the procedure in all four patients lasted between 10 and 15 min, and the authors stated that the use of endoscopic guidance prevented damage to the posterior tracheal wall and helped in identifying the puncture site thanks to transillumination. Currently, the “routine” use of endoscopic guidance as part of percutaneous tracheostomy is controversial [ 10 – 13 ] and guidelines cannot establish recommendation levels [ 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%